Two-stage treatment of ametropia in patients with keratoconus and cataracts - M. M. Bikbov; O. I. Orenburkina; A. E. Babushkin; I. F. Nuriev (Acta Biomedica Scientifica)
Keratoconus (KC) is a progressive degenerative corneal disease, leads to the aberration of biomechanical and optical properties and thinning of the cornea, causes astigmatism and decreases visual acuity.Materials and methods. 33 patients (35 eyes) with stages II–III of non-progressive keratoconus and concomitant cataracts of various stages of maturity were operated on. The average age of the patients was 46.5 ± 2.7 (41–63) years old. The operations were performed according to our proposed two-stage method of treating ametropia in patients with KC and cataracts (Patent of the Russian Federation No. 2748634 of 28.05.2021). The first stage was the implantation of FERRARA intrastromal corneal ring segments (ICRS) with thickness from 150 to 350 μm. To correct residual refractive error in 5–7 months after stage 1, patients underwent stage 2: cloudy lens was removed and replaced with toric posterior chamber intraocular lens (TIOL) – AcrySof IQ Toric (Alcon, USA), T-fl ex Toric RayOne (Rayner, UK).Results and discussion. After stage 1 of the operation (ICRS implantation), the uncorrected visual acuity (NCVA) was 0.2 ± 0.03, the best corrected visual acuity (BCVA) was 0.4 ± 0.02. In 1 month after stage 2 (phacoemulsifi cation + TIOL) NCVA was 0.64 ± 0.11 and BCVA was 0.74 ± 0.12. During the entire follow-up period after the surgery visual functions, refraction, and rotational stability of TIOL were stable.Conclusions. Conducting a two-stage surgical intervention in patients with keratoconus and cataracts allows to stop the progression of the disease and effectively correct the ametropia concomitant with keratoconus.